(untitled) (Jurnal Agribisnis dan Agrowisata, 2025)
Rahayu Group in Joho Village Kalidawir Subdistrict Tulungagung Regency. Rahayu Group is formed based on The Prosperous Family Income Improvement Program by KB Village. The purpose of this research is to find out the empowement effort of women farmer who make gadung’s chips on Rahayu Group in Joho Village, Kalidawir Subdistrict, Tulungagung Regency, according to four empowerment. The sample size are 38 members of Rahayu Group. Collecting data methods include (1) Interviews with respondents and key informants (2) Observations (3) Documentation. Data analysis include quantitative analytics and qualitative analytics. Based on all of the empowerment effort of women farmer who make gadung’s chips on Rahayu Group by human empowerment, business empowerment, environment empowerment, and organization empowerment it could be said that empowerment are in good categories. It can be proved that most of women farmer have could implement the substance to be gained during empowerment process into home industry individually nor is on organization. The advice that can be given in this study i.e do business trip to a succesful gadung’s chips home industry in another place, women farmer who make gadung’s chips can consider to applying for a loan to grow their business, and the department of agriculture can provide guidance for organic fertilization and giveaways of gadung tuber seedlings, Rahayu Group makes the written rules and norms. As well as to the next researcher can explorer empowerment aspect and empowerment object.